Challenges in Conducting Action Research: Experiences from Biology Teachers of a Province in Mindanao, Philippines - Cortes, Sylvester Tan; Reyes, Jr., Margarito Surbito (Jurnal Pendidikan Progresif, 2021)
Abstract: Challenges in Conducting Action Research: Experiences from Biology Teachers of a Province in Mindanao, Philippines. Objectives: This study aimed to explore biology teachers’ experiences from a province in Mindanao regarding their challenges while engaging in action research. Methods: It employed a multiple case studies method that involved detailed examination and in-depth analysis of primary and secondary data collected from questionnaires, in-depth individual interviews, and other relevant artifacts from the participants. Findings: Teacher’s major challenges in action research (AR) are reported as themes, namely: negative perceptions and attitudes, lack of conceptual knowledge and unresponsive nature to critiques, lack of time and resources, and mistrust of colleagues’ research capacity. Conclusion: The professional development programs these teachers previously attended did not upgrade their skills in AR because of the following reasons: rolled out in a short period, episodic, had minimal scaffolding and monitoring, and lack evaluation of teachers’ AR projects after the training programs. Keywords: action research, biology teachers, challenges, professional development. DOI: http://dx.doi.org/10.23960/jpp.v11.i2.202102